Potential impact of lady beetles on Diaphorina citri (Homoptera: Psyllidae) in Puerto Rico - Michaud, J. P.; Pluke, Richard W. H.; Escribano, Ana; Stansly, Philip A. (My University, 2008)
The first detections of Asian citrus psyllid, Diaphorina citri Kuwayama, in North America occurred almost simultaneously in Florida and in the Caribbean (Guadeloupe). Damaging populations on citrus have been reported in Florida but not in Puerto Rico where the psyllid was first detected in 2001, having probably arrived with its parasitoid, Tamarixia radiate Waterston. In an effort to identify additional sources of mortality, the relative abundance of coccinellid species was estimated on 180 citrus trees from early April to early July 2003. The most abundant species were Coelophora inaequalis F. (38.8%) and Cycloneda sanguinea limbifer L. (31.3%), and the least abundant were Cladis nitidula F. (5.9%), Coleomegilla innonata Mulsant (4.8%), Chilocorus cacti L. (2.1%), Scymnus sp. (5.9%), Hippodamia convergens Guerin (2.4%), and Cryptolaemus montrouzieri Mulsant (8.8%). These eight species were collected from citrus production areas in Puerto Rico for a laboratory study of feeding behavior. All eight consumed D. citri nymphs, with C. innonata consuming psyllids at a greater rate than C. cacti or Scymnus sp. Choice tests showed that C. inaequalis and C. s. limbifer preferred brown citrus aphid (BCA) Toxoptera citricida to D. citri as prey, whereas C. nitidula and C. cacti (both Chilochorini) preferred D. citri . Our results suggest that coccinellid species could play an important role as predators of the psyllid in Puerto Rico and contribute to its natural control.
Citation: Pluke, Richard W. H., Ana Escribano, J. P. Michaud, and Philip A. Stansly. 2005. “POTENTIAL IMPACT OF LADY BEETLES ON DIAPHORINA CITRI (HOMOPTERA: PSYLLIDAE) IN PUERTO RICO.” Florida Entomologist 88 (2): 123–28. https://doi.org/10.1653/0015-4040(2005)088[0123:PIOLBO]2.0.CO;2.
Keywords: Asian citrus psyllid; Coccinellidae; Predator; Relative abundance; Feeding behavior; Natural control